Evaluasi Kegiatan Peningkatan Pengetahuan Masyarakat Tentang Pelaksanaan Pemilihan Gubernur Tahun 2020 - Effendi, Desrian; Effendi, M. Yusrizal (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Kesbangpol is one of the parties involved or responsible for supporting the implementation of the 2020 Riau Islands Governor election. The task of the Tanjungpinang City Kesbangpol is to assist the Mayor in administering Regional Government and implementing regional policies in the fields of National Unity, Domestic Politics and Community Empowerment. The study was to determine the evaluation of Community Knowledge Improvement Activities regarding the Implementation of the 2020 Governor Election. The researcher uses the concept of CIPP policy evaluation by Stufflebeam. This type of research is evaluative with a qualitative approach. The population of this research is the Kesbangpolpenmas Agency of Tanjungpinang City and 500 participants based on the attendance of participants in the activity to increase public knowledge about the 2020 Governor election. The sample technique used is purposive sampling. The data used are primary and secondary data, where the data collection techniques are observation, interviews, and documentation. Data analysis was carried out by qualitative analysis. The results of the research can be concluded that the first is related to participants in the Public Awareness Improvement activity regarding the Implementation of the 2020 gubernatorial election is still low. Suggestions should be that the time allocated for training is longer and divided by sub-districts will be more effective.